The Influence of The Strategic Position of Indonesia in The South China Sea Toward The Military Partnership Between Indonesia And China in 2010-2015 - Zuhri, Ahmad Syaifuddin; Hanifa (Journal of Indonesian Social Sciences and Humanities, 2017)
This article aims to analyze the strategic position of Indonesia in South China Sea (SCS) towards the military partnership of Indonesia and China from 2010-2015. The aim of this research is to analyze how the strategic position of Indonesia influences the military relationship between Indonesia and China. The South China Sea is one of the most strategic and influential regions; it has the capability to threaten the stability of Southeast Asia. Indonesia as one of the most significant countries in ASEAN geographically, has a strategic but conflicted position. This research will analyze how the strategic position of Indonesia in the SCS influences their military partnership with China. This research formulates questions as to how the Indonesian strategic position in the South China Sea influences the China-Indonesia military relationship in 2010-2015? This article a neo-realist theory, a national security concept and a geo-strategic concept to accomplish this. It also uses a qualitative method of analysis through research papers and holding interviews. Through the three concepts and school of thought, this research has found that there is an influence on the strategic position of Indonesia in the militaristic relationship between Indonesia and China. The strategic location of Indonesia in the South China Sea and the significant role Indonesia plays in ASEAN can positively affect the relationship between Indonesia and China.